Duck gut viral metagenome analysis captures snapshot of viral diversity. Issue 1 (December 2016) - Fawaz, Mohammed; Vijayakumar, Periyasamy; Mishra, Anamika; Gandhale, Pradeep; Dutta, Rupam; Kamble, Nitin; Sudhakar, Shashi; Roychoudhary, Parimal; Kumar, Himanshu; Kulkarni, Diwakar; Raut, Ashwin
Abstract Background Ducks (Anas platyrhynchos ) an economically important waterfowl for meat, eggs and feathers; is also a natural reservoir for influenza A viruses. The emergence of novel viruses is attributed to the status of co-existence of multiple types and subtypes of viruses in the reservoir hosts. For effective prediction of future viral epidemic or pandemic an in-depth understanding of the virome status in the key reservoir species is highly essential. Methods To obtain an unbiased measure of viral diversity in the enteric tract of ducks by viral metagenomic approach, we deep sequenced the viral nucleic acid extracted from cloacal swabs collected from the flock of 23 ducks which shared the water bodies with wild migratory birds. Result In total 7, 455, 180 reads with average length of 146 bases were generated of which 7, 354, 300 reads werede novo assembled into 24, 945 contigs with an average length of 220 bases and the remaining 100, 880 reads were singletons. The duck virome were identified by sequence similarity comparisons of contigs and singletons (BLASTx E score,  <10−3 ) against viral reference database. Numerous duck virome sequences were homologous to the animal virus of thePapillomaviridae family; and phages of theCaudovirales, Inoviridae, Tectiviridae, Microviridae families and unclassified phages. Further, several duck virome sequences had homologous with the insect viruses of thePoxviridae, Alphatetraviridae, Baculoviridae, Densovirinae, Iflaviridae andDicistroviridae families; and plant viruses of theSecoviridae, Virgaviridae, Tombusviridae andPartitiviridae families, which reflects the diet and habitation of ducks. Conclusion This study increases our understanding of the viral diversity and expands the knowledge about the spectrum of viruses harboured in the enteric tract of ducks.